Procedure Optimization for Organic Ambipolar Transistor: Laterally Aligned Micro n-/p-Channels via Dry Soft-Lithographic Process - Oh, Sangyoon; Park, Sang Kyu; Park, Soo Young (WILEY, 2022)
In spite of the large potential of ambipolar transistors constituted of laterally aligned unipolar n-/p-channel semiconductors, it is hard to secure the full electrical performance of each semiconductor channel by the risk of intermixing which leads to low crystallinity. Here, a novel fabrication process of patterned taping is proposed which ensures the formation of sharp interface and thus preserving the original performance of individual channels-laterally aligned micro n-/p-channels via all-dry soft-lithographic process. Different from other bi-component active layer devices, such as vertically stacked n-/p-bilayer and n-/p-blend film, laterally aligned n-/p-channel of this work secures clear ambipolarity because both the n-/p-channels are directly laid over a common gate dielectric surface. Essentially, laterally aligned n-/p-channels constructed by patterned taping are free from lateral channel mixing or broadening effect different from other processes such as wet-processing and fine metal mask (FMM) patterning. In this work, a novel patterned taping method of laterally aligned n-/p-channel transistors and also their optimized transistor performances compared with other bi-component devices using the same set of n- and p-type semiconductor materials is demonstrated.